Հայկական արդիականացումը որպես Հայոց ցեղասպանության պատճառ (Ադանայի օրինակով) - Մանուկյան, Սուրեն (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
In the beginning of XX century the difference between retarded Moslem and modernized, innovative Armenian communities was clearly visible. This gap brought envy and hatred against the Armenians and became one of the reasons of 1909 Adana massacres.
Keywords: Հայոց ցեղասպանություն; Հայոց պատմություն